2001
DOI: 10.1104/pp.126.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lipid Metabolic Enzymes during the Endoplasmic Reticulum Stress Response in Plants

Abstract: The endoplasmic reticulum (ER) stress response is a signal transduction pathway activated by the perturbation of normal ER metabolism. We used the maize (Zea mays) floury-2 (fl2) mutant and soybean (Glycine max) suspension cultures treated with tunicamycin (Tm) to investigate the ER stress response as it relates to phospholipid metabolism in plants. Four key phospholipid biosynthetic enzymes, including DG kinase and phosphatidylinositol (PI) 4-phosphate 5-kinase were upregulated in the fl2 mutant, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 44 publications
5
47
0
1
Order By: Relevance
“…Mouse embryo fi broblast culture cells transfected with the active form of XBP1 showed an enhanced activity of CCT (Sriburi et al, 2004). This result is in agreement with the fact that the CCT activity in protein bodies of fl oury-2 maize also increases when UPR is activated (Shank et al, 2001). Furthermore, Arabidopsis thaliana culture cells treated with salycilic acid leads to the upregulation of the ER stress markers BiP3 and PDI as well as the PI 4-kinase (Krinke et al, 2007), enzyme that is also activated in fl oury-2.…”
Section: Figure 2 Schematic Representation Of the Involvement Of Uprsupporting
confidence: 78%
See 2 more Smart Citations
“…Mouse embryo fi broblast culture cells transfected with the active form of XBP1 showed an enhanced activity of CCT (Sriburi et al, 2004). This result is in agreement with the fact that the CCT activity in protein bodies of fl oury-2 maize also increases when UPR is activated (Shank et al, 2001). Furthermore, Arabidopsis thaliana culture cells treated with salycilic acid leads to the upregulation of the ER stress markers BiP3 and PDI as well as the PI 4-kinase (Krinke et al, 2007), enzyme that is also activated in fl oury-2.…”
Section: Figure 2 Schematic Representation Of the Involvement Of Uprsupporting
confidence: 78%
“…In fact, the synthesis of this mutated form of α-zein triggers ER stress since a high expression of the BiP gene can be observed both in fl oury-2 and transgenic maize that harbor the mutated form of this α-zein. But in addition to these early observations, an interesting phenomena was described by Shank et al (2001), who observed a modifi cation in the synthesis of lipids in the fl oury-2 maize due to the upregulation of four enzymes involved in lipids synthesis -diacylglycerol (DG) kinase, phosphatidylinositol (PI) 4-phosphate 5-kinase, cholinephosphate cytidylyltransferase (CCT) and PI 4-kinase-. In addition, they found a signifi cant increase in the incorporation of radiolabeled acetate into phospholipids of soybean culture cells treated with tunicamycin, suggesting that activation of the UPR is linked to an increase in phospholipid biosynthesis.…”
Section: Figure 2 Schematic Representation Of the Involvement Of Uprmentioning
confidence: 99%
See 1 more Smart Citation
“…2 suggests that PLD␤ is active at resting Ca 2ϩ levels, this is unlikely to be the case in vivo, where PIP 2 levels are lower than those present in the substrate vesicles used for our in vitro activity assay (36). Our previous studies clearly demonstrate the concentration-dependent activation of PLD␤ by PIP or PIP 2 (3,4,16) and, like Ca 2ϩ , cellular levels of these signaling molecules increase in response to external stimuli and stress (37). In addition, although increased PIP 2 levels increase the binding of PLD␤cat to PC, PLD␤-C2 domain binding to PC is not stimulated by PIP 2 at any concentration (16).…”
Section: Fig 2 Pld Activities Of Gst-pld␤ and Gst-pld␤cat And Theirmentioning
confidence: 99%
“…Lipid metabolism and ER stress We used both maize and soybean systems to investigate the ER stress response as it relates to phospholipid metabolism in plants (Shank et al, 2001). We made the key discovery that inducing a strong unfolded protein response (UPR) in the ER leads to an increase in triacylglycerol and phospholipid accumulation in endosperm, and a change in signaling kinases.…”
Section: Major Findingsmentioning
confidence: 99%